Correlation analysis and clinical significance of CA125, HE4, DDI, and FDP in type II epithelial ovarian cancer. Issue 49 (4th December 2020) - Qiao, Li; Chen, Xinhua; Xi, Xuxia; Chen, Xueqin; Zhang, Pengpeng; Dong, Hua; Wu, Xiaohua; Chen, Xiaojun
Abstract : Abstract: Ovarian cancer is one of the common female malignant tumors. The early diagnosis and treatment of ovarian cancer has been a research hotspot. Therefore, we aimed to investigate the correlations between the levels of carbohydrate antigen 125 (CA125), human epididymis protein 4 (HE4), D-dimer (DDI), and fibrinogen degradation product (FDP) in patients with type II epithelial ovarian cancer. From January 2018 to January 2019, a total of 952 patients who underwent initial surgery for epithelial ovarian cancer were enrolled in this study. Peripheral venous blood was taken before operation, and the levels of CA125, HE4, DDI, and FDP were tested. The correlations between the levels of CA125, HE4, DDI, and FDP and other clinical indicators (such as presence or absence of chemotherapy, surgical conditions) were analyzed. The level of DDI or FDP was statistically associated with age, chemotherapy, Figo staging, surgical procedure, HE4 level, and CA125 level, respectively. Moreover, the Figo staging was statistically correlated with the levels of HE4 and CA125. Besides, we found the levels of CA125 and HE4 were positively correlated with the levels of DDI and FDP. The levels of CA125 and HE4 are the traditional detection indexes for patients with type II epithelial ovarian cancer, and these 2 indicators reflected the degree of disease and prognosis. The levels of DDI and FDP were closely related to the levels of CA125 and HE4 in type II epithelial ovarian cancer, and they also helped to assess the prognosis of epithelial ovarian cancer. Further larger-scale prospective cohort studies are warranted to determine these associations in the future.